2003
DOI: 10.1080/03009740310003767
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐U1RNP antibody and aseptic meningitis in connective tissue diseases

Abstract: SLE or MCTD patients with aseptic meningitis tend to have anti-U1RNP antibody.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Some studies have determined the presence of anti-U1RNP antibody [30] and have found high serum procalcitonin levels (≥0.5 ng/ml) [31]. It has been suggested that these methods may be useful to discriminate between septic and aseptic meningitis; however, few data exist for patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have determined the presence of anti-U1RNP antibody [30] and have found high serum procalcitonin levels (≥0.5 ng/ml) [31]. It has been suggested that these methods may be useful to discriminate between septic and aseptic meningitis; however, few data exist for patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have clearly indicated that anti-ribosomal P [9,10] and anti-NR2 [11] Abs are linked to the depression-type psychiatric disorder and cognitive dysfunction, respectively. In addition, it has been reported that connective tissue disease (CTD) patients with aseptic meningitis tend to have anti-U1RNP Abs in the Japanese population [2]. CSF-anti-U1RNP Abs may have an important role in MCTD-associated aseptic meningitis in Case 2 because anti-U1RNP IgG Abs appeared to be more concentrated in CSF than in serum, especially in the acute phase.…”
Section: Discussionmentioning
confidence: 97%
“…In sera from Japanese aseptic meningitis patients with CTD, anti-U1RNP Abs are frequently recognized [2]. Several NSAIDs and other drugs induce aseptic meningitis, especially in patients with systemic lupus erythematosus (SLE) and MCTD [3].…”
Section: Introductionmentioning
confidence: 99%
“…4 Arinuma et al 5 reported that anti-NR2 Abs in the cerebrospinal fluid (CSF), but not in serum, were involved in diffuse central NPSLE. Okada et al 6 reported that 13 of 14 patients (seven SLE, five mixed connective tissue disease (MCTD) or overlap syndrome, one undifferentiated CTD, one Sjo¨gren's syndrome) with aseptic meningitis attributed to CTD had serum anti-U1 ribonucleoprotein (RNP) Abs. Recently, using an RNA-immunoprecipitation assay (RNA-IPP), we found that anti-U1RNP Abs were detected in CSF; anti-U1RNP Abs in CSF could be a useful biomarker of NP manifestations in SLE.…”
Section: Introductionmentioning
confidence: 99%